Gitanos y payos. Dos mundos y dos ideas sobre la libertad en “la Gitanilla” - Iribarren, Mary C. (THÉMATA. Revista de Filosofía, 2008)
Gitanos y payos. Dos mundos y dos ideas sobre la libertad en “la Gitanilla”